High quality genome assembly and annotation (v1) of the eukaryotic terrestrial microalga Coccomyxa viridis SAG 216-4 - Kraege, Anton; Chavarro-Carrero, Edgar A.; Guiglielmoni, Nadège; Schnell, Eva; Kirangwa, Joseph; Heilmann-Heimbach, Stefanie; Becker, Kerstin; Köhrer, Karl; Schiffer, Philipp; Thomma, Bart P. H. J.; Rovenich, Hanna (Peer Community Journal, 2024)

(untitled)
Unicellular green algae of the genus Coccomyxa are recognized for their worldwide distribution and ecological versatility. Most species described to date live in close association with various host species, such as in lichen associations. However, little is known about the molecular mechanisms that drive such symbiotic lifestyles. We generated a high-quality genome assembly for the lichen photobiont Coccomyxa viridis SAG 216-4 (formerly C. mucigena). Using long-read PacBio HiFi and Oxford Nanopore Technologies in combination with chromatin conformation capture (Hi-C) sequencing, we assembled the genome into 21 scaffolds with a total length of 50.9 Mb, an N50 of 2.7 Mb and a BUSCO score of 98.6%. While 19 scaffolds represent full-length nuclear chromosomes, two additional scaffolds represent the mitochondrial and plastid genomes. Transcriptome-guided gene annotation resulted in the identification of 13,557 protein-coding genes, of which 68% have annotated PFAM domains and 962 are predicted to be secreted.